Petrology and oxygen isotopic compositions of calcium‐aluminum‐rich inclusions in primitive CO3.0‐3.1 chondrites. (5th May 2020) - Zhang, Mingming; Bonato, Enrica; King, Ashley J.; Russell, Sara S.; Tang, Guoqiang; Lin, Yangting
Abstract: The petrologic and oxygen isotopic characteristics of calcium‐aluminum‐rich inclusions (CAIs) in CO chondrites were further constrained by studying CAIs from six primitive CO3.0‐3.1 chondrites, including two Antarctic meteorites (DOM 08006 and MIL 090010), three hot desert meteorites (NWA 10493, NWA 10498, and NWA 7892), and the Colony meteorite. The CAIs can be divided into hibonite‐bearing inclusions (spinel‐hibonite spherules, monomineralic grains, hibonite‐pyroxene microspherules, and irregular/nodular objects), grossite‐bearing inclusions (monomineralic grains, grossite‐melilite microspherules, and irregular/nodular objects), melilite‐rich inclusions (fluffy Type A, compact type A, monomineralic grains, and igneous fragments), spinel‐pyroxene inclusions (fluffy objects resembling fine‐grained spinel‐rich inclusions in CV chondrites and nodular/banded objects resembling those in CM chondrites), and pyroxene‐anorthite inclusions. They are typically small (98.4 ± 54.4 µm, 1SD) and comprise 1.54 ± 0.43 (1SD) area% of the host chondrites. Melilite in the hot desert and Colony meteorites was extensively replaced by a hydrated Ca‐Al‐silicate during terrestrial weathering and converted melilite‐rich inclusions into spinel‐pyroxene inclusions. The CAI populations of the weathered COs are very similar to those in CM chondrites, suggesting that complete replacement of melilite by terrestrial weathering, and possibly parent body aqueous alteration, would make the CO CAIs CM‐like, supporting the hypothesis that CO and CM chondrites derive from similar nebular materials. Within the CO3.0‐3.1 chondrites, asteroidal alteration significantly resets oxygen isotopic compositions of CAIs in CO3.1 chondrites (∆ 17 O: −25 to −2‰) but left those in CO3.0‐3.05 chondrites mostly unchanged (∆ 17 O: −25 to −20‰), further supporting the model whereby thermal metamorphism became evident in CO chondrites of petrologic type ≥3.1. The resistance of CAI minerals to oxygen isotope exchange during thermal metamorphism follows in the order: melilite + grossite < hibonite + anorthite < spinel + diopside + forsterite. Meanwhile, terrestrial weathering destroys melilite without changing the chemical and isotopic compositions of melilite and other CAI minerals.